PENGARUH SISTEM PENGAWINAN (INSEMINASI BUATAN DAN ALAMI) DAN PARITAS INDUK BABI TERHADAP LITTER SIZE DI USAHA PETERNAKAN BABI PT. ADHI FARM, SOLO - Maria Herawati (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2017)
The aims of this study was to determine the optimal litter size which produce from the mating system and the sow parity by noticing the litter size born alive, the age of weaning, litter size at weaning, mortality during the suckling period and litter size at weaning percentage. Fourty one farrowing and weaned sows are used in this research. The first factor is the mating system, included artificial insemination and natural service. The second factor is the parity of the sow (1 up to 5). The data collected were litter size born alive, the age of the weaning, the weaned litter size, mortality of the suckling period and litter size at weaning percentage.The result showed that the mating system had significant effect (P0.05) on the age of the weaning, the litter size at weaning, mortality during the sucling period and litter size at weaning percentage. The parity had significantly effect (P0.05) on the litter size born alive, mortality during the sucling period and litter size at weaning percentage. The interaction between the mating system and the parity was significantly effected (P